Downregulation of serum miR-30c-5p serves as a biomarker to predict disease onset and short-term prognosis in acute coronary syndrome patients - Bo Chang; Xiangfeng Zhang; Riliang Fang; Huibin Li; Youdan Zhou; Yakun Wang (Journal of Cardiothoracic Surgery)
Abstract Background & objective Timely intervention for Acute coronary syndrome (ACS) could effectively reduce the mortality rate of ACS patients. This study aimed to investigate the clinical significance of miR-30c-5p for ACS and to provide a convenient biomarker for diagnosing of ACS. Methods Baseline information was collected from a total of 173 subjects (98 ACS subjects and 65 healthy subjects). The miR-30c-5p expression was evaluated by the Polymerase chain reaction (PCR). The predictive value of miR-30c-5p for ACS was assessed by Receiver Operating Characteristic (ROC) curve and multivariate logistic regression analysis. The relationship between miR-30c-5p expression and ACS severity was assessed by correlation analysis. Furthermore, the prognostic value of miR-30c-5p on Major Adverse Cardiovascular Events (MACE) occurrence was assessed by the Kaplan-Meier (K-M) curve to evaluate its prognostic significance. Results Downregulation of miR-30c-5p was observed in ACS subjects and its diagnostic value on ACS was confirmed by the ROC curve. MiR-30c-5p could also discriminate acute myocardial infarction (AMI) from unstable angina pectoris (UAP) subjects in ACS. The expression of miR-30c-5p was negatively correlated with the cardiac troponin I (cTnI) levels and the Gensini score. A lower miR-30c-5p expression was observed in ACS subjects who developed MACE (P = 0.020), and the K-M curve further confirmed the close correlation between miR-30c-5p expression and MACE occurrence in ACS. MiR-30c-5p was also identified as an independent prognostic factor for MACE in ACS. Conclusions Serum miR-30c-5p expression was correlated with the severity of ACS, and downregulated miR-30c-5p expression showed a diagnostic and prognostic value in ACS.